The Invariable Nature of Territory - Sequeira, Marta (Dafne, 2015)
In various writings, interviews, classes, and conferences, João Luís Carrilho da Graça insists on the importance of identifying the exact nature of a certain territory in order to execute an architectural design. In his text “Metamorphosis”, he explains at length that this need reflects the continuity of human action over time. He shows that the ridge lines and valleys, and the mains points of the topography serve as the basis for human journeys and settlements, and thus, the building of cities and their architecture. These topographical points correspond in general to notable edifices and spaces, and “the lines that are geographically and topographically dedicated to paths for crossing and access are necessarily of a more public nature and tend to be registered physically upon the territory, defining the limits and the formal structure of the anthropised space.
Keywords: Carrilho da Graça; Lisboa; Território; Paisagem; Século XX; Século XXI